Digital Transformation and Governance in MSMEs: Qualitative Perspectives on Financial Accountability in Banten, Indonesia - Sri Lestari (Yayasan Aya Sophia Indonesia, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in Indonesia’s economic and social development; however, the implications of digital transformation for governance and financial accountability remain insufficiently understood, particularly from a contextual perspective. This study aims to explore how digital transformation reshapes governance practices and financial accountability in MSMEs in Banten, Indonesia. Using a qualitative interpretive case study approach, data were collected through in-depth interviews, observations, and document analysis involving MSME owners and managers. The findings reveal that digital transformation is primarily adopted as a pragmatic response to operational needs, enabling improved financial visibility, transaction traceability, and internal accountability. Nevertheless, governance structures remain informal, centralized, and relational, with accountability largely oriented toward trust-based relationships rather than formal regulatory compliance. Theoretically, this study advances the literature on digital transformation, governance, and accountability by challenging corporate-centric assumptions that equate digitalization with formalized governance, and by demonstrating how digital accountability is socially embedded within informal governance systems of MSMEs in developing economies. Practically, the findings provide insights for policymakers, financial institutions, and MSME support organizations to design context-sensitive digital governance initiatives that strengthen accountability without imposing rigid reporting requirements that may burden small enterprises.